Portrait du philosophe en forme de singe - Dominique Lestel (Revue de Primatologie)
Why do primatologists and anthropologists belong to different disciplines? This question convokes fundamental epistemic characteristics of both disciplines. It would be naïve to believe that goodwill would be sufficient to obtain a salutary convergence. The realist-cartesian paradigm of today’s ethology cannot be conciliated with the notion of meaning, which is central in anthropology. The animal is always studied as a bearer of qualities that interest primatologists, such as memory, predatory strategies etc., instead of being considered through its existence. I suggest that it is possible to conceive other ways to practice primatology (for instance through a bi-constuctivist paradigm), which would give a central importance to the notion of meaning. However, hoping for this perspective is still illusionary.